Deletion of Schizophrenia Susceptibility Gene Ulk4 Leads to Abnormal Cognitive Behaviors via Akt-GSK-3 Signaling Pathway in Mice. (6th May 2022) - Hu, Ling; Zhou, Bing-Yao; Yang, Cui-Ping; Lu, Da-Yun; Tao, Yun-Chao; Chen, Lin; Zhang, Lei; Su, Jun-Hui; Huang, Ying; Song, Ning-Ning; Chen, Jia-Yin; Zhao, Li; et al.
Abstract: Objectives: Despite of strenuous research in the past decades, the etiology of schizophrenia (SCZ) still remains incredibly controversial. Previous genetic analysis has uncovered a close association of Unc-51 like kinase 4 (ULK4), a family member of Unc-51-like serine/threonine kinase, with SCZ. However, animal behavior data which may connect Ulk4 deficiency with psychiatric disorders, particularly SCZ are still missing. Methods: We generated Emx1-Cre:Ulk4 flox/flox conditional knockout (CKO) mice, in which Ulk4 was deleted in the excitatory neurons of cerebral cortex and hippocampus. Results: The cerebral cellular architecture was maintained but the spine density of pyramidal neurons was reduced in Ulk4 CKO mice. CKO mice showed deficits in the spatial and working memories and sensorimotor gating. Levels of p-Akt and p-GSK-3α/β were markedly reduced in the CKO mice indicating an elevation of GSK-3 signaling. Mechanistically, Ulk4 may regulate the GSK-3 signaling via putative protein complex comprising of two phosphatases, protein phosphatase 2A (PP2A) and 1α (PP1α). Indeed, the reduction of p-Akt and p-GSK-3α/β was rescued by administration of inhibitor acting on PP2A and PP1α in CKO mice. Conclusions: Our data identified potential downstream signaling pathway of Ulk4, which plays important roles in the cognitive functions and when defective, may promote SCZ-like pathogenesis and behavioral phenotypes in mice.